ANALISA BAKTERI PADA KARANG SCLERACTINIA BERKAITAN DENGAN FENOMENA LA-NINA DI KAWASAN TAMAN NASIONAL BUNAKEN - AMPOU, EGHBERT ELVAN; TRIYULIANTI, IIS; NUGROHO, SUCIADY C. (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2012)
Research about Scleractinian Coral with bacteria contamination are relatively new explore in Indonesia. The research study was located in Bunaken National Park in period May 2010 and August 2011. Research focused on gram positive ( +) and gram negative (-) bacteria. For sampling procedure by using SCUBA equipment with time swim at depth 5 - 10 meters at least 30 minutes and collected randomly coral mucus. In the Laboratory sample anlayzed by Isolate bactery process. For the result we noticed that on May 2010 gram positive bacteria are dominant, otherwise in August 2011 gram negative bacteria more dominant. Were indicated influence by La-Nina phenomenon during 2010 until earlier 2011 that seasonal transition I (May) and Monsoon II (August) is sigfnificantly different. For the future need to be explore especially to determine species of bactery and seasonal sampling.
Keywords: Bactery, Scleractinian coral, gram positive, gram negative, La-Nina.